Moderate prenatal alcohol exposure was associated with a modest increase in adolescent learning and behavioural difficulties [commentary on Olson HC, Streissguth AP, Sampson PD, et al. Association of prenatal alcohol exposure with behavioral and learning problems in early adolescence. J AM ACAD CHILD ADOLESC PSYCHIATRY 1997 Sep;36:1187-94]. - Hellerstedt WL (Evidence Based Nursing, 1998)
Objective: To determine whether an association exists between prenatal alcohol exposure and behavioural and learning difficulties in early adolescence. Design: Population based cohort study from the Seattle Longitudinal Prospective Study on Alcohol and Pregnancy. Setting: USA. Participants: 250 infants of women who reported social alcohol use during pregnancy and 250 infants of women who reported infrequent or no alcohol use during pregnancy were selected in 1974-5 and followed up to a mean age of 14.5 years. Mothers were predominantly white, married, middle class, 20-30 years of age, and at low risk for adverse pregnancy outcomes. 249 boys and 215 girls completed the 14 year follow up. Assessment of risk factors: Mothers were interviewed during the fifth month of pregnancy about early and mid-pregnancy alcohol use, demographics, pregnancy history, nutrition, and use of caffeine, tobacco, and illicit and prescription drugs. Net prenatal alcohol exposure was assigned a composite score based on the weighted average of 13 consumption scores. 78% of mothers reported some drinking during mid-pregnancy. The median consumption for a drinker was approximately 1 half ounce drink of alcohol per day before recognition of pregnancy and less than a quarter ounce of alcohol per day during mid-pregnancy. 'Drinkers' ingested an average of 2 to 2.5 drinks per occasion before pregnancy recognition and less than 2 drinks per occasion during mid-pregnancy. 39% of mothers reported at least one instance of 'binge' drinking (>/= 5 drinks per occasion) early in pregnancy and 24% reported this during mid-pregnancy. Main outcome measures: At the 14 year follow up, data on adolescent learning and behaviour were collected by adolescent self report (questionnaires given by a research examiner during a 4 h clinic session), parent report (structured telephone interviews and posted Child Behaviour Checklist), and research examiner report (Behaviour Rating Form based on the 4 h of clinic testing). The researcher was unaware of the adolescent's prenatal alcohol exposure, previous test results, and home environment. Net learning and behaviour difficulty was assigned a composite score based on the weighted average of 186 items reported by the adolescent, parent, and research examiner. Main results: The unadjusted correlation between prenatal alcohol exposure and adolescent difficulties was 0.31. Increased alcohol dose was generally associated with increased difficulties; however, not all exposed adolescents had problems and associations were highly variable. Stepwise multiple regression techniques were used to adjust for child sex, maternal education, presence of 2 parents in the home at ages 4 and 14 years, and household smoking. After adjusting for covariates, the correlation between prenatal alcohol exposure and adolescent difficulties was 0.20. There were no interactions between these covariates and prenatal alcohol exposure. Conclusion: Moderate prenatal alcohol exposure was associated with a modest increase in adolescent learning and behavioural difficulties.